Relationship Between Patients' Anxiety Levels Before Open Heart Surgery With Postoperative Symptoms - Dilek Aygin; Özge Yaman (Sakarya University, 2022)
Objective: It was aimed to assess the relationship between patients' anxiety levels before open heart surgery with postoperative pain, dyspnea, and nausea-vomiting in this study. Method(s): The study was performed between September 2017 and April 2018 with 77 patients who underwent open heart surgery after obtaining ethical approval. Before the surgery, the "Anxiety Specific to Surgery Questionnaire" and patient information forms were completed, while after the surgery, the "Visual Analogue Scale for Pain", the "Modified Borg Scale" and the "Rhodes Index of Nausea, Vomiting, and Retching" were implemented within three days after the patients were discharged from the intensive care unit to follow-up services. Results: The average age of the patients was 58.63±11.85; 72.7% of the patients were male and 46.8% were overweight. The patients were determined to experience medium-level anxiety before open heart surgery. The total anxiety and nausea-vomiting-retching distress scores obtained by the females were higher than those obtained by the males. A positive statistical correlation was detected in mid-levels between pain and dyspnea and in low levels between pain and nausea-vomiting. Conclusion: The patients were determined to experience medium-level anxiety before open heart surgery, and it was found that there was no relationship between anxiety and pain, dyspnea, or nausea-vomiting.